2012
DOI: 10.1093/carcin/bgs152
|View full text |Cite
|
Sign up to set email alerts
|

The environmental stressor ultraviolet B radiation inhibits murine antitumor immunity through its ability to generate platelet-activating factor agonists

Abstract: Ubiquitous pro-oxidative stressor ultraviolet B radiation (UVB) to human or mouse skin generates platelet-activating factor (PAF) and novel oxidatively modified glycerophosphocholines (Ox-GPCs) with PAF-receptor (PAF-R) agonistic activity. These lipids mediate systemic immunosuppression in a process involving IL-10. The current studies sought to determine the functional significance of UVB-mediated systemic immunosuppression in an established model of murine melanoma. We show that UVB irradiation augments B16F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(139 citation statements)
references
References 47 publications
4
134
1
Order By: Relevance
“…As shown in Figure 1, exogenous administration of CPAF augments the growth of subcutaneously implanted LLC1 tumors in WT but not in PAFR-KO mice, which indicates that this effect is mediated via the host PAF-R. These results are consistent with our previous reports demonstrating that UVB/CPAF augments the growth of murine B16F10 tumors in a PAF-R-dependent manner 19. These studies also indicate that PAF-R agonist-mediated systemic immunosuppression is not specific in augmenting the growth of experimental melanoma tumors; however, it can also affect the growth of lung cancer.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure 1, exogenous administration of CPAF augments the growth of subcutaneously implanted LLC1 tumors in WT but not in PAFR-KO mice, which indicates that this effect is mediated via the host PAF-R. These results are consistent with our previous reports demonstrating that UVB/CPAF augments the growth of murine B16F10 tumors in a PAF-R-dependent manner 19. These studies also indicate that PAF-R agonist-mediated systemic immunosuppression is not specific in augmenting the growth of experimental melanoma tumors; however, it can also affect the growth of lung cancer.…”
Section: Resultssupporting
confidence: 92%
“…Functional PAF-R in LLC1 cells was accessed by intracellular Ca 2+ mobilization assay as described previously 19,20. In brief, LLC1 tumor cells, grown at optimum condition, were loaded with the Ca 2+ - sensitive fura-2-AM dye (4 μM in Hanks’ balanced salt solution [HBSS]) at 37°C for 90 min.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, our studies have shown that PAF-induced immunosuppression promotes the growth of syngeneic tumors in mice [19]. Thus, the ability of topical CPAF to suppress chemical carcinogenesis in mice would run counter to previous thoughts regarding the role of PAF in tumorigenesis.…”
Section: Discussioncontrasting
confidence: 55%
“…9,105,106 PAF and PAFR agonists are generated after exposure to oxidative stress and inhibit the antitumor immune response. 107 In an animal model of lung cancer, administration of PAFR agonists led to increased tumor growth and lung metastasis. 106 In a recent animal study the oxidative stress of traditional chemotherapy promoted PAF production and subsequent treatment failure, suggesting a role for PAF signaling in treatment outcomes.…”
Section: Malignancymentioning
confidence: 99%